在包络跟踪功率放大中的包络整形的方法和设备 (2020)
本文所描述的主题涉及在包络跟踪功率放大中的包络整形。提供了一种用于在包络跟踪功率放大中的包络整形的方法、设备和计算机存储介质。在一个实施方案中，所述方法包括：在时域中对参考包络信号执行包络整形操作，以获得经过整形的包络信号；在频域中对经过整形的包络信号执行信号质量控制；以及将经过整形的包络信号从频域变换到时域，以获得结果的经过整形的包络信号。以此方式，可以提供更好的信号质量而无需对接收机侧进行任何修改。并且继而所述包络信号的PAPR可以在进入包络跟踪电源调制器之前得到降低，而且ET电源调制器的效率可以得到改进。其结果是，ET PA系统的性能得以提高。 The subject matter described herein relates to envelope shaping in envelope tracking power amplification. A method, apparatus and computer storage medium are provided for envelope shaping in envelope tracking power amplification. In an embodiment, the method comprises performing an envelope shaping operation on reference envelope signals in a time domain to obtain shaped envelope signals; performing a signal quality control on the shaped envelope signals in a frequency domain; and converting the shaped envelope signals from the frequency domain into the time domain to obtain resulting shaped envelope signals. In such a way, a better signal quality can be provided without any modifications to the receiver side. And in turn, the PAPR of